2020
DOI: 10.3389/fmicb.2020.01808
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Rhodococcus opacus R7 Grown on o-Xylene by RNA-Seq

Abstract: Xylenes are considered one of the most common hazardous sources of environmental contamination. The biodegradation of these compounds has been often reported, rarer the ability to oxidize the ortho-isomer. Among few o-xylene-degrading bacteria, Rhodococcus opacus R7 is well known for its capability to degrade diverse aromatic hydrocarbons and toxic compounds, including o-xylene as only carbon and energy source. This work shows for the first time the RNA-seq approach to elucidate the genetic determinants involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The number of genes was varied greatly in the two groups, indicating that the inhibitory effect of the CHEC on B. dothidea was very strong. This result was similar to that of the experiment conducted by Zampolli et al (2020). The total number of differential genes was 20,510 (included genes expressed in the control group and those not expressed in the treatment group), of which the number of down‐regulated genes reached 19,139, while the number of up‐regulated genes was only 1371.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The number of genes was varied greatly in the two groups, indicating that the inhibitory effect of the CHEC on B. dothidea was very strong. This result was similar to that of the experiment conducted by Zampolli et al (2020). The total number of differential genes was 20,510 (included genes expressed in the control group and those not expressed in the treatment group), of which the number of down‐regulated genes reached 19,139, while the number of up‐regulated genes was only 1371.…”
Section: Resultssupporting
confidence: 92%
“…The number of genes was varied greatly in the two groups, indicating that the inhibitory effect of the CHEC on B. dothidea was very strong. This result was similar to that of the experiment conducted by Zampolli et al (2020). The total number of differential genes was 20,510 (included genes expressed in the The different color curves correspond to different experimental results of samples in (Figure 8a).…”
Section: Genes Differentially Expressed Analysissupporting
confidence: 85%
“…Abnormal LogFC values were shown by 19 differentially expressed genes (DEGs) due to the switch-off/-on effect 48 , thus they were corrected with a min-value approximation resulting in an approximated LogFC varying from − 20 to 21. Among the 19 DEGs with corrected LogFC, 5 were up-regulated genes, 14 were down-regulated genes, and 11 genes were preliminary annotated as hypothetical proteins (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Members of the genus Rhodococcus are often reported as effective o-xylene degraders, 1−3 and their o-xylene metabolism has been deeply studied. 4 Nevertheless, results of a recent enrichment study suggested that members of the genus Rhodococcus prefer clear aerobic conditions for the degradation of petroleum hydrocarbons and are marginalized under microaerobic conditions. 5 Since subsurface environments are naturally oxygen-limited, we sought to determine which bacterial lineages play a role in the aerobic degradation of xylene under limited oxygen availability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although m -xylene- and p -xylene-degrading bacteria are frequently reported, those bacteria which can use the ortho isomer of xylene as their sole source of carbon and energy are seemingly much rarer. Members of the genus Rhodococcus are often reported as effective o -xylene degraders, and their o -xylene metabolism has been deeply studied . Nevertheless, results of a recent enrichment study suggested that members of the genus Rhodococcus prefer clear aerobic conditions for the degradation of petroleum hydrocarbons and are marginalized under microaerobic conditions .…”
Section: Introductionmentioning
confidence: 99%